ANALISIS PENYELESAIAN TINDAK LANJUT HASIL PEMERIKSAAN AUDITOR INSPEKTORAT DAERAH PROVINSI SULAWESI UTARA - Rondonuwu, Albert Otniel; Manossoh, Hendrik; Wokas, Heince R. N. (Universitas Sam Ratulangi, 2022)
This study aims to analyze the kamislot completion of the follow-up to the results of supervision/inspection in the LHP Inspectorate by the Regional Apparatus Organization of North Sulawesi Province. This research uses a qualitative approach with a case study method. This study was conducted to investigate in depth and conduct an analysis of OPD compliance (auditee) in the completion of follow-up by the subjects in this study/the parties involved in the implementation of the TLHP settlement in accordance with the recommendations contained in the LHP of the Regional Inspectorate of North Sulawesi Province. The results of this study indicate that the examination carried out by the Regional Inspectorate Auditor of North Sulawesi Province is used as an evaluation material for the implementation of OPD programs/activities. The completion of the TLHP is carried out in the form of coordination with related parties, the findings of financial management that become regional financial losses are the main obstacles to settlement. TLHP and requires a relatively longer time in order to carry out the completion of the TLHP.